Solution processable inverted type perovskite solar cells - Alishan, Hamed Moeini (My University, 2021)
For more than one decade, perovskite-based solar cells have attracted considerable attention due to its particular features, which include low price, long carrier diffusion length, high absorption coefficient, low-temperature preparation, low charge recombination, high electron and hole mobility, controllable bandgap, and a fast improvement from 3.9 % to more than 25%, which is not typical for solar cells to progress so quickly in such a short time. In perovskite solar cells, charge transport layers (CTL) are significantly vital to the device's performance. Therefore, choosing a suitable and cost-effective CTL is inevitable. Despite being one of the most commonly applied hole transporters in solar cell research, PEDOT:PSS must still meet the performance criteria of solar cells. Consequently, PEDOT: PSS has become of the most popular due to its improved morphology, conductivity, and durability. In this thesis by using a simple method we investigate the performance of PSCs when PEDOT: PSS layers are exposed to UV radiation. In addition, the influence of dopants also on electro-optical properties and performance of PEDOT: PSS based perovskite solar cells has been investigated. Bathocuproine (BCP) is a well-known material used in perovskite solar cells as a hole-blocking layer. Vacuum or solution processing can be used to process thin BCP films as buffer layers. In this thesis, the effect of BCP layers prepared using sol-gel method on the performance of perovskite solar cells is investigated. On the other hand, inorganic charge transport materials are preferred because they are plentiful, inexpensive, and have high hole mobility and chemical stability. Because of its high optical transmittance, broad direct bandgap, deep valance band, and high conduction band, non-stoichiometric nickel oxide (NiOx) is widely used as a HTL for inverted PSCs. For the first time in the literature, we demonstrate a research based on Ce and Zn co-doping into NiOx HTLs for inverted type PSCs.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2021
Keywords: Perovskite solar cells; BCP; PEDOT:PSS; NiOX